Validation of a palliative care outcome measurement tool supplemented by neurological symptoms (HOPE+): Identification of palliative concerns of neurological patients - Dillen, Kim; Ebke, Markus; Koch, Andreas; Becker, Ingrid; Ostgathe, Christoph; Voltz, Raymond; Golla, Heidrun (Palliative Medicine, 2019)
Background: There is growing interest to integrate palliative care and its structures into the care of neurological patients. However, in Germany there is no comprehensive assessment tool capturing the symptoms of patients with advanced neurological diseases. Aim: To validate a newly developed palliative care measurement tool based on an extension of the validated core documentation system Hospice and Palliative Care Evaluation considering additional neurological issues (HOPE+). Design: Prospective, observational study using HOPE+ and as external criteria, the Eastern Cooperative Oncology Group (ECOG) performance status and the 12 months “surprise” question (12-SQ) in a neurological population, and assessment for its construct validity and diagnostic accuracy. Setting/participants: All newly admitted patients to the Department of Neurorehabilitation, Dr. Becker Rhein-Sieg-Clinic aged 18–100 years (#DRKS00010947). Results: Data from 263 patients (63 ± 14 years of age) were analyzed. HOPE+ revealed a moderately correlated six-factor structure (r = –0.543–0.525). Correlation analysis to evaluate discriminant validity using ECOG as external criterion was high (rs(261) = 0.724, p < 0.001) and confirmed for severely affected patients by adding the 12-SQ (“No”-group: 48.00 ± 14.92 vs “Yes”-group: 18.67 ± 7.57, p < 0.009). Operating characteristics show satisfactory diagnostic accuracy (area under the curve: 0.746 ± 0.049, 95% confidence interval = 0.650–0.842). Conclusion: HOPE+ demonstrates promising psychometric properties. It helps to assess palliative care issues of patients in neurological settings and, in combination with the 12-SQ, conceivably conditions when to initiate the palliative care approach in a population underrepresented in palliative care structures so far.
CRIS-Team Scopus Importer:2019-07-23
Keywords: neurological patients; outcome measurement; Palliative care concerns; prospective observational design; symptom burden; validation